2020
DOI: 10.1371/journal.pone.0232985
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-mediated ablation of overexpressed EGFR in combination with sunitinib significantly suppresses renal cell carcinoma proliferation

Abstract: Receptor tyrosine kinases, such as VEGFR, PDGFR and EGFR, play important roles in renal cancer. In this study, we investigated EGFR knockout as a therapeutic approach in renal cell carcinoma (RCC). We showed that a renal cell carcinoma cell line (RC21) has higher expression of EGFR as compared to other frequently used cell lines such as HEK293, A549, Hela and DLD1. Ablation of EGFR by CRISPR/Cas9 significantly restrained tumor cell growth and activated the MAPK (pERK1/2) pathway. The VEGFR and PDGFR inhibitor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…They found that CRISPR-mediated ablation of overexpressed EGFR in combination with sunitinib could significantly improve the therapeutic effect of sunitinib. Interestingly, the loss of EGFR eventually induced resistance to SAHA and cisplatin ( 156 ). Several studies have also shown that the EGFR status is associated with drug resistance in cancer, which suggests that EGFR knockout RC21 cells could be a cisplatin-resistant cell model.…”
Section: Transgenic Drug Resistance Modelsmentioning
confidence: 99%
“…They found that CRISPR-mediated ablation of overexpressed EGFR in combination with sunitinib could significantly improve the therapeutic effect of sunitinib. Interestingly, the loss of EGFR eventually induced resistance to SAHA and cisplatin ( 156 ). Several studies have also shown that the EGFR status is associated with drug resistance in cancer, which suggests that EGFR knockout RC21 cells could be a cisplatin-resistant cell model.…”
Section: Transgenic Drug Resistance Modelsmentioning
confidence: 99%
“…Liu et al used CRISPR/Cas9 technology to create renal cell carcinoma (RCC) cell lines with EGFR knockout, which significantly inhibited cancer cell proliferation and induced cell arrest in the G2/M phase. However, knocking out EGFR resulted in high ERK expression, but the authors discovered that ERK and Akt could be inhibited by Sunitinib (a multi-targeted TKI) in combination ( Liu et al, 2020 ), suggesting that CRISPR mediated knockout of drug resistance genes may be a promising option for future disease treatment.…”
Section: Principles Of Multidrug Resistance In Nsclc Reversed By Cris...mentioning
confidence: 99%
“…In addition to it is overexpression in breast cancer. [9] FDA approved several drugs targeting EGFR such as sorafenib I [13], sunitinib II [14], erlotinib [15] III (Figure 1), lapatinib [16], gefitinib [17] and osimertinib [18]. Most of these developed drugs usually binds to ATP active site of EGFR-TK.…”
Section: Introductionmentioning
confidence: 99%